مصنوعی ذہانت کے ذریعے اقبال کی نظم ”مسجدِ قرطبہ“ کا کارپس لسانیات کی رو سے تجزیہ: IQBAL POEM ‘‘MASJID-E-QURTABA’’ CORPUS LINGUISTIC ANALYSIS VIA AI TOOL (Al-Aasar, 2026)
This article presents a corpus-linguistic analysis of Allama Muhammad Iqbal’s long poem “Masjid-e-Qurtaba” using modern Artificial Intelligence (AI) tools. Through the scientific methodology of corpus linguistics, the research examines word frequency, collocations, repetition patterns, keywords, semantic fields, metaphorical and syntactic structures within the poem. The analysis reveals that concepts such as love (Ishq), time, and the ideal believer (Mard-e-Momin) occupy central positions, while the use of Arabic and Persian vocabulary enriches the linguistic style with grandeur and semantic depth. The poem’s oratorical tone, dialogic elements, and repetitive structures enhance its cognitive and aesthetic impact. Corpus-based findings demonstrate that “Masjid-e-Qurtaba” is not only representative of Iqbal’s philosophical vision but also an exemplary model of linguistic experimentation and creative innovation in Urdu poetry. This study highlights the potential of AI-assisted tools for exploring new research avenues in digital Urdu linguistics.